160k views
3 votes
Find dy du , du dx , and dy dx .

(a) y = u5 and u = x2 + 1 dy du = du dx = dy dx =

(b) y = u4 and u = 4x2 − x + 6 dy du = du dx = dy dx =

User Eugenecp
by
6.0k points

2 Answers

2 votes

Answer:

have fun with the answer just want some points

Explanation:

User MarkSkayff
by
5.8k points
4 votes

Answer:

a)
(dy)/(du)=5(x^2 +1)^4,
(du)/(dx)=2x,
(dy)/(dx)=10x(x^2+1)^4

b)
(dy)/(du)=4(4x^2-x+6)^3,
(du)/(dx)=8x-1,
(dy)/(dx)=4(8x-1)(4x^2-2+6)^3

Explanation:

We can use the chain rule in the following form: is u=u(x) is a differentiable function depending on x and y=y(u) is a differentiable function depending on u, then
(dy)/(dx)=(dy)/(du) (du)/(dx).

a)
(dy)/(du)=(d)/(du) (u^5)=5u^4=5(x^2 +1)^4 from the power rule.


(du)/(dx)=(d)/(dx) (x^2 +1)=2x.

From the previous parts and the chain rule,
(dy)/(dx)=(dy)/(du) (du)/(dx)=5(x^2 +1)^4(2x)=10x(x^2+1)^4

b)
(dy)/(du)=(d)/(du) (u^4)=4u^3=4(4x^2-x+6)^3


(du)/(dx)=(d)/(dx) (4x^2-x+6)=8x-1 from the power and sum rules.

Then,
(dy)/(dx)=(dy)/(du) (du)/(dx)=4(4x^2 -x+6)^3(8x-1)=4(8x-1)(4x^2-x+6)^3

User Ifusion
by
5.3k points